Hubungan Efikasi Diri, Strategi Koping Dan Motivasi Berprestasi dengan Kejenuhan Akademik Mahasiswa pada Pembelajaran Daring - Ramadhanti, Desviana Herlien; Pratisti, Wiwien Dinar (Abdi Psikonomi, 2023)
This research is focused on student academic burnout which is a problem for students in implementing online learning activities during the Covid-19 pandemic. Based on the literature review, self-efficacy, coping strategies and achievement motivation are thought to be factors that influence academic burnout in college students. The purpose of this study was to determine the relationship: self-efficacy, coping strategies and achievement motivation with academic burnout in college students, self-efficacy with academic burnout in college students, coping strategies with academic burnout in college students, achievement motivation with academic burnout in college students. This study uses a correlational quantitative approach and the population is college students of Muhammadiyah University of Surakarta with simple random sampling technique. Analysis of the data obtained using the SPSS program. The results of this study indicate that: there is a very significant relationship between self-efficacy, coping strategies and achievement motivation with academic burnout in college students, there is a significant negative relationship between self-efficacy and academic burnout in college students, there is a very significant negative relationship between coping strategies with academic burnout in college students, there is a significant negative relationship between achievement motivation with academic burnout in college students. The results of the study showed that: 1) self-efficacy contributed 6.6% to academic burnout, 2) coping strategies contributed 3.37% to academic burnout, 3) achievement motivation contributed 16.5% to academic burnout. The effective contribution of the research variables is 26.5%, so the other 73.5% is influenced by other variables such as self-esteem, trait-anxiety, personality characteristics, and others.